2010
DOI: 10.1021/pr100394u
|View full text |Cite
|
Sign up to set email alerts
|

An Informatics-assisted Label-free Quantitation Strategy that Depicts Phosphoproteomic Profiles in Lung Cancer Cell Invasion

Abstract: Aberrant protein phosphorylation plays important roles in cancer-related cell signaling. With the goal of achieving multiplexed, comprehensive, and fully automated relative quantitation of site-specific phosphorylation, we present a simple label-free strategy combining an automated pH/acid-controlled IMAC procedure and informatics-assisted SEMI (sequence, elution time, mass-to-charge, and internal standard) algorithm. The SEMI strategy effectively increased the number of quantifiable peptides more than 4-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 76 publications
1
53
0
Order By: Relevance
“…Quantitative Analysis by IDEAL-Q-The quantitative analysis of phosphopeptides was performed with the SEMI label-free algorithm (34) and IDEAL-Q software (35). The raw data files acquired from the LTQ-Orbitrap were converted into files of mzXML format by the program ReAdW (XCalibur, Thermo Finnigan), and the search results in MASCOT were exported in Extensible Markup Language data (.xml) format.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative Analysis by IDEAL-Q-The quantitative analysis of phosphopeptides was performed with the SEMI label-free algorithm (34) and IDEAL-Q software (35). The raw data files acquired from the LTQ-Orbitrap were converted into files of mzXML format by the program ReAdW (XCalibur, Thermo Finnigan), and the search results in MASCOT were exported in Extensible Markup Language data (.xml) format.…”
Section: Methodsmentioning
confidence: 99%
“…It also demonstrated that Cdc14 is a major phosphatase in the cell cycle. To identify potential Cdc14 substrates, we filtered the cdc14-1/CDC14 ratio with a threshold of 2-fold determined from the technical replicate (34). A total of 835 dephosphorylation sites on 455 potential Cdc14 substrates showed a Ͼ2-fold increase in cdc14-1 cells in vivo (Fig.…”
Section: Large-scale Identification Of Potential Substrates Of Cdc14mentioning
confidence: 99%
“…The enriched samples were subjected to liquid chromatography-coupled tandem mass spectrometry (LC-MS/MS) analysis using a NanoAcquity system (Waters) connected to an LTQ-Orbitrap XL hybrid mass spectrometer (Thermo Fisher Scientific) equipped with a nanospray interface (Proxeon). The quantitative analysis was as described previously with minor modifications [25,26]. Raw MS/MS data were converted into peak lists (MGF file) using Raw2MSM [27] with default parameters.…”
Section: Phosphopeptide Analysismentioning
confidence: 99%
“…The phosphopeptides enriched from non-, IgG1-, and DcR3-treated cell lysates were analyzed by LC-MS/MS, and a total of 1887 phosphopeptides derived from 826 proteins were identified. Based on the standard deviation of our label-free quantitation strategy [25], phosphopeptides showing more than twofold changes in abundance compared to control were considered as the altered phosphorylation sites with either upregulation or downregulation. Among all the identified phosphopeptides (n=1887), 532 phosphopeptides from 319 proteins were modulated in DcR3-Mϕ [i.e., with at least twofold of up-or downregulation of expression ratio (DcR3 versus IgG1-treatment)], while ratio in the control group (IgG1 versus non-treated group) did not show any statistically significant change before IAV infection.…”
Section: Quantitative Phosphoproteomic Profiling Of Dcr3-treated Macrmentioning
confidence: 99%
“…One site, serine 391, which has been identified in proteomic analyses of mitotic phosphoproteins (Daub et al, 2008;Dephoure et al, 2008;Olsen et al, 2010;Wang et al, 2010), is followed by Fig. 2.…”
Section: Crm1 Localizes To Spindle Microtubules and Kinetochores In Mmentioning
confidence: 99%